2020
DOI: 10.1016/j.heliyon.2020.e03244
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory evoked magnetic fields of periodontal mechanoreceptors

Abstract: To evaluate the localization of responses to stimulation of the periodontal mechanoreceptors in the primary somatosensory cortex, somatosensory evoked fields (SEFs) were measured for stimulation of the left mandibular canine and first molar using magnetoencephalography in 25 healthy subjects. Tactile stimulation used a handmade stimulus device which recorded the trigger at the moment of touching the teeth.SEFs for the canine and first molar were detected in 20 and 19 subjects, respectively. Both responses were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The restored trigeminal proprioceptive pathway together with its specialized sensory discriminative features could further be corroborated in preclinical animal models using electroencephalographic, magnetoencephalographic 63 and fMRI approaches 64…”
Section: Discussionmentioning
confidence: 95%
“…The restored trigeminal proprioceptive pathway together with its specialized sensory discriminative features could further be corroborated in preclinical animal models using electroencephalographic, magnetoencephalographic 63 and fMRI approaches 64…”
Section: Discussionmentioning
confidence: 95%
“…Against our hypothesis, we did not find a significant correlation between MP and EC of the S1, even though its activation has been consistently found during a chewing task (Lin, 2018). Both animal and human research revealed that during mastication, S1 activity was associated with the processing of mechanosensation, the major source of sensory feedback from the peripheral site (Hihara et al, 2020; Kaneko et al, 2017). Therefore, the S1 may play an essential role in maintaining normal mastication.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, fibers reach the VPM to innervate as 'barreloids' the thalamic nucleus (Erzurumlu et al, 2010) from r3 projections, while the spinal fibers enter as the contralateral medial lemniscus (SpV, gracile, and cuneate) to innervate the VPL (Iwasato and Erzurumlu, 2018). Interesting bilateral information is described in gums and teeth that show faster ipsilateral projections in humans and monkeys (Andrew et al, 2020;Hihara et al, 2020). We have a somatosensory, topological innervation (Figures 1A, 5A) to project to the mammalian cortex with a primary and secondary innervation giving rise to the SOC from r4/5.…”
Section: The Thalamus Receives the Topological Somatosensory Inputsmentioning
confidence: 99%